2005
DOI: 10.1007/bf03167022
|View full text |Cite
|
Sign up to set email alerts
|

Structural and dynamic properties of polyoxyethylene sorbitan monooleate micelle in water dispersion studied by pulsed field gradient NMR

Abstract: The diffusion phenomenon of a nonionic surfactant, polyoxyethylene sorbitan monooleate (POE-SMO), micelle in aqueous solution was investigated by pulsed field gradient nuclear magnetic resonance (PFG NMR) with a high gradient strength of 17.4 T/m at the diffusion time t d varied from 3 to 300 ms. This high gradient strength allowed us to measure the slow self-diffusion coefficient of POE-SMO micelle, and the short diffusion time below 10 ms showed the restricted diffusion of the micelle. At the short t d the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The slow water diffusion coefficients below 10 -11 m 2 /s could be measured by our PFG-NMR, showing the microscopic water diffusion. The high maximum gradient strength should be used to measure the water diffusion coefficients below 10 -9 m 2 /s due to the fast exchange between exchangeable protons and water molecules as reported in our previous study (the water exchange in surfactant-water micelle systems) (27). Therefore, the two water states around the protein matrix were well-characterized by the Ka ¨rger model (22), even though the chemical exchange on the pore surfaces with water molecules in the tofu was not measured due to the inhomogeneity.…”
Section: A(g)mentioning
confidence: 99%
“…The slow water diffusion coefficients below 10 -11 m 2 /s could be measured by our PFG-NMR, showing the microscopic water diffusion. The high maximum gradient strength should be used to measure the water diffusion coefficients below 10 -9 m 2 /s due to the fast exchange between exchangeable protons and water molecules as reported in our previous study (the water exchange in surfactant-water micelle systems) (27). Therefore, the two water states around the protein matrix were well-characterized by the Ka ¨rger model (22), even though the chemical exchange on the pore surfaces with water molecules in the tofu was not measured due to the inhomogeneity.…”
Section: A(g)mentioning
confidence: 99%
“…Overlooking lipid diffusion could result in a reduction of the self-diffusion coefficient of water in starch granule by an order of magnitude of 10 À11 m 2 /s compared to that of 10 À10 m 2 /s in this study. Hong, Kim, Volkov, Skirda, and Lee (2005) reported that proton exchange between a water molecule and a surfactant OH group on the micelle surface was observed using PFG-NMR with a maximum gradient strength of 17.4 T/m and with the shortest diffusion time of 3 ms. Proton exchange on the micelle was proposed in the region of restricted diffusion with the size of 0.8-1.8 lm where the spatial network or the micellar clustering could be form. Furthermore, the exchange lifetime of the proton on the micelle surface was estimated to be about 8.0 ms, based on the longitudinal magnetization decay with the spin-lattice relaxation time (T 1 ).…”
Section: Ricementioning
confidence: 98%
“…Another reason of population p 1 reducing is a spin–lattice relaxation. Therefore, the p 1 ( t d ) is a biexpontial shape [ 178 ]: where τ is the lifetime of the molecule; T 1 is a spin–lattice relaxation time, which is ≈600 ms; p s , p f are the weights of a slow and fast components, respectively. Figure 64 shows the dependence p 1 (t d ) and its decomposition into components in accordance with Equation (11).…”
Section: Biological Systems: Protein and Cell Membranesmentioning
confidence: 99%